2019
DOI: 10.1017/s0007114518003501
|View full text |Cite
|
Sign up to set email alerts
|

Oat bran, but not its isolated bioactiveβ-glucans or polyphenols, have a bifidogenic effect in anin vitrofermentation model of the gut microbiota

Abstract: Wholegrain oats are known to modulate the human gut microbiota and have prebiotic properties (increase the growth of some health-promoting bacterial genera within the colon). Research to date mainly attributes these effects to the fibre content; however, oat is also a rich dietary source of polyphenols, which may contribute to the positive modulation of gut microbiota. In vitro anaerobic batch-culture experiments were performed over 24 h to evaluate the impact of two different doses (1 and 3 % (w/v)) of oat br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 85 publications
1
37
0
1
Order By: Relevance
“…Moreover, some of the nonfiber components, sometimes referred to as co‐passengers, also may have biological activity (Fardet, 2010; X. Liu, Le Bourvellec, et al., 2020). For instance, in an elegant study, oat bran (including the co‐passengers) has been shown to be effective in increasing Bifidobacterium populations in the gut, whereas the purified bioactive β‐glucans did not show a bifidogenic effect (Kristek et al., 2019). Nevertheless, some interesting research has been performed on whole grains.…”
Section: Effects Of Whole Grain On Microbiota Composition and Activitymentioning
confidence: 99%
“…Moreover, some of the nonfiber components, sometimes referred to as co‐passengers, also may have biological activity (Fardet, 2010; X. Liu, Le Bourvellec, et al., 2020). For instance, in an elegant study, oat bran (including the co‐passengers) has been shown to be effective in increasing Bifidobacterium populations in the gut, whereas the purified bioactive β‐glucans did not show a bifidogenic effect (Kristek et al., 2019). Nevertheless, some interesting research has been performed on whole grains.…”
Section: Effects Of Whole Grain On Microbiota Composition and Activitymentioning
confidence: 99%
“…As whole-grain cereals are also rich sources of dietary fibers, it is controversial whether these effects were solely due to the phenolic compounds alone [109]. In an in vitro fermentation simulating the digestion from mouth to small intestine, Kristek et al [110] studied the impact of 1% and 3% intake of oat bran, β-glucan extract, and polyphenol extracts separately. The results showed that the polyphenol mix increased the Enterobacteriaceae family within 24 h, but the most significant impact (increment of bifidobacteria, enhanced production of propionic and acetic acid) on the gut microbiota was achieved with the digestion of oats and not by a single group of compounds; this implies a synergistic effect of the dietary fibers and polyphenols on gut microbiota and also points to the lack of energy for microbial growth in the case of using single compounds as substrates.…”
Section: Prebiotic Potential Of Cereal-based Fermented Foodsmentioning
confidence: 99%
“…A recent study using an in vitro batch culture system demonstrated that oat β-glucan induced proliferation of Bacteroidetes but was not Bifidogenic. In contrast growth of Bifidobacteria was stimulated by oat-derived polyphenols (82). In another study oat flakes promoted growth of the Bacteroides/Prevotella group or Bifidobacterium group in a fecal slurry with effects related to the size of the oat flakes (31).…”
Section: Alternative Mechanisms By Which Oat β-Glucan May Affect Hostmentioning
confidence: 99%